Strategi Komunikasi Digital dalam Konteks Bisnis Modern - Ineez Alex Sangkaropi; Divara Sasyabilla Nur; Sem Janwar Tampang; Devin Lolo Padang; Mada Aditia Wardhana (TEKNOBIS : Jurnal Teknologi, Bisnis dan Pendidikan, 2026)
Digital communication strategies have become a crucial pillar in the modern business context, providing a framework for organizations to manage their image, interactions, and relationships with stakeholders. This article aims to analyze two critical aspects of these strategies: first, the effectiveness of digital leadership framing strategies employed by corporate leaders on social media compared to traditional media; and second, the role of virtual agent (chatbot) personalization strategies through the provision of avatar choices and anthropomorphic design in mitigating the uncanny valley effect (the feeling of discomfort toward imperfect human likeness) in the e-commerce context. The study was conducted using a systematic method comprising a preparation phase, article searches from academic databases, data analysis using separate matrices, and thematic synthesis. The findings reveal that on social media, leaders tend to adopt higher levels of analytical thinking and a more positive tone to build closeness and avoid reputational risks, in contrast to the more formal approach observed in traditional media. Meanwhile, chatbot personalization through avatar selection has been shown to foster consumers’ psychological ownership, effectively reducing uncanny valley sensations, enhancing trust, and ultimately promoting loyalty and purchase intention. These findings imply that adapting communication strategies to the characteristics of the medium and empowering users through personalization are key to success in today’s digital business landscape.